Tank Man, Media Memory and Yellow Duck Patrol: Remembering Tiananmen on social media. Issue 5 (3rd July 2016) - Ibrahim, Yasmin
Abstract : Tiananmen Square is a compressed and repressed space of memories and histories. It is symbolic of different forms of collective forgetting and remembering for the Chinese state and a monumental space of global spectatorship. In 2013, the commemoration of the 24th anniversary of the Tiananmen Massacre of 1989 in Sina Weibo (the Chinese version of Twitter), demonstrated how people negotiated state censorship to remember the event. This social media commemoration was both an act of resistance against the state's imposition of an official memory and equally a means to thwart censorship through creative expression, particularly in the form of the image. The commemoration of Tiananmen online nevertheless highlighted the hegemony of media memory where it was entrapped through the iconic image of the Tank Man. The Tank Man as a meme on social media was both a phantom place memory of Tiananmen as well as a cultural artefact re-imagined through the ludic and visual architecture of Web 2.0.